TechTIM By CML at The National Science Week Carnival 2023 - Hafizoah, Kassim; Wan Jumani, Fauzi (Pusat Bahasa Moden (PBM), 2023)
15 November 2023 – The National Science Week Carnival 2023, finally reached its last leg at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Pekan campus, on 10 – 11 November 2023. The event was organised by the Ministry of Science, Technology, and Innovation (MOSTI) in a collaborative effort with Pejabat Setiausaha Kerajaan Negeri Pahang.